If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-3) = (-3) + 1 Reorder the terms for easier multiplication: -3f = (-3) + 1 -3f = -3 + 1 Combine like terms: -3 + 1 = -2 -3f = -2 Solving -3f = -2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-3'. f = 0.6666666667 Simplifying f = 0.6666666667
| y(9x-2y)dx-x(6x-y)dy=0 | | 2x+20=3x+50 | | (u-4)*10=40 | | 4x=8x+7 | | 3x-7+9x-2+x+7=180 | | 3y+y^2=35 | | 3x+4=(6x+5)-3x | | 5f-160=9c | | 2x+49=7x+4 | | 5x+9x+3=-39 | | 3*(4/3) | | 16/9=42/x | | 26/34-8 | | 7x+56=90 | | 6n-3=6 | | 6n-3=4 | | 169=42x | | 4/3•3.14•474.552 | | 9+35g=11-0.5g | | 9x+16-8x=-2+(-12) | | -7x+7+8x=-5+19 | | 10x+1+6x-4=77 | | x=0.998x | | 5x+124=180 | | (2.5x^2)+500x+20000=0 | | 9/2x(-1/9) | | 3n-19=26 | | e^5-3/5 | | 40x+15(1.5x)=547.47 | | 7n=28.7 | | -3(w-9)=-8w+2 | | 64x^3=16x |